Let's destroy work, let's destroy the economy - Bonanno, Alfredo M., 1937-2023 (London : Ardent Press, 2013)
The old work ethic has disappeared along with the massive obsolete structures of capital which required a permanent army of producers, yet work still has far more implications than mere survival. Millions of people still compete for the privilege of turning up day after day, year after year, to surrender body and soul in exchange for a wage. The alternative: to encounter one's real desires and create the means required to realise them, could present some surprises and lead to undreamed choices. A job, boring or arduous as it might be, is the easy way out. It gives structure to our day and puts order in our expectations, giving us just enough in our pockets to acquire instant sublimation and quell any sudden surge of hatred towards what is stealing our time and our lives.